2022
DOI: 10.1111/bjd.21687
|View full text |Cite
|
Sign up to set email alerts
|

Distinct skin microbiome community structures in congenital ichthyosis

Abstract: Background The ichthyoses are rare genetic keratinizing disorders that share the characteristics of an impaired epidermal barrier and increased risk of microbial infections. Although ichthyotic diseases share a T helper (Th) 17 cell immune signature, including increased expression of antimicrobial peptides, the skin microbiota of ichthyoses is virtually unexplored. Objectives To analyse the metagenome profile of skin microbiome for major congenital ichthyosis subtypes. Methods Body site‐matched skin surface sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
1
14
3
Order By: Relevance
“…Prior to this study, there was limited data to understand the microbiome and immunological signatures accompanying the various ichthyoses, and even less data across races or ethnicities. We note after preparation of this report a microbiome study on 22 CI patients from 4 types (Congenital ichthyosiform erythroderma (CIE), LI, EI, Netherton’s Syndrome (NS)) was published [26]. Using WES we fully characterized the mutations underlying disease in 36 CI patients belonging to 7 CI types with Southeast Asian ethnicity, identifying 20 novel variants.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, there was limited data to understand the microbiome and immunological signatures accompanying the various ichthyoses, and even less data across races or ethnicities. We note after preparation of this report a microbiome study on 22 CI patients from 4 types (Congenital ichthyosiform erythroderma (CIE), LI, EI, Netherton’s Syndrome (NS)) was published [26]. Using WES we fully characterized the mutations underlying disease in 36 CI patients belonging to 7 CI types with Southeast Asian ethnicity, identifying 20 novel variants.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermolytic Ichtyosis (EI), Netherton syndrome (NS) lamellar ichtyosis and congenital ichtyosiform erythroderma (CIE) are known to show the highest prevalence. Lipidomics analysis of skin surface samples from ichtyosis patients and controls showed that the skin microbiome is markedly altered from healthy skin, and specific alterations predominate in various ichtyosis subtypes [ 130 ].…”
Section: Lipid*omic*s In Rare Diseasesmentioning
confidence: 99%
“…In this issue of the BJD, Tham and colleagues profiled the skin microbiome of 22 subjects with congenital ichthyoses compared with healthy controls. 3 This study investigated the skin microbiome of four types of congenital ichthyosis [autosomal recessive congenital ichthyosis (ARCI): congenital ichthyosiform erythroderma (CIE), lamellar ichthyosis (LI), epidermolytic ichthyosis (EI) and Netherton syndrome (NS)] in order to investigate potential differences in microbiome composition between subtypes. Subjects with and without ichthyosis were sampled by skin swab at body site-matched locations (scalp, upper arm, upper buttock) and wholemetagenomics sequencing analysis was performed to profile the bacteria, fungi and viruses.…”
Section: Ian Coulson Idmentioning
confidence: 99%
“…Based on their findings and prior studies, 6,7 Tham and colleagues propose an interesting hypothesis, namely, that increased relative abundance of Staphylococcus, Corynebacterium, Malassezia and Trichophyton species contribute to the known Thelper (Th)17 immune polarization in disorders of cornification. 3 All these organisms are known to activate the Th17 pathway and contribute to skin inflammation in other contexts, but have not been previously described in ichthyosis. It is also possible that increased skin inflammation and barrier disruption further contribute to microbial dysbiosis in these patients, creating a chronic inflammatory cycle.…”
Section: Ian Coulson Idmentioning
confidence: 99%
See 1 more Smart Citation